2023
DOI: 10.1039/d2sc04124c
|View full text |Cite
|
Sign up to set email alerts
|

Time- and angle-resolved photoemission spectroscopy (TR-ARPES) of TMDC monolayers and bilayers

Abstract: Many unique properties in two-dimensional (2D) materials and their heterostructures rely on charge excitation, scattering, transfer and relaxation dynamics across different points in the momentum space. Understanding of these dynamics...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 145 publications
(215 reference statements)
1
4
0
Order By: Relevance
“…Thus, this behavior is identical to what occurs in all pump-probe experiments that have used other non-optical probing techniques such as time-and angle-resolved photoemission spectroscopy [TrARPES, also known as two-photon photoemission spectroscopy (2PPES)] [ [14][15][16][17][18][19][20][21][22][23], time-resolved x-ray diffraction [41,42] and time-resolved conductivity [43]. Although all probing methods reflect the influence of pump-excited carriers on semiconductor properties, only 2PPES and one-photonpumped TA spectroscopy (1PPTAS) allow one to study the evolution of the electron energy distribution function (EDF) during the relaxation process [14][15][16][17][18][19][20][21][22][23]37]. In addition to elucidating the carrier cooling mechanism, EDF also provides valuable information about the possible states of carriers in semiconductor devices.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Thus, this behavior is identical to what occurs in all pump-probe experiments that have used other non-optical probing techniques such as time-and angle-resolved photoemission spectroscopy [TrARPES, also known as two-photon photoemission spectroscopy (2PPES)] [ [14][15][16][17][18][19][20][21][22][23], time-resolved x-ray diffraction [41,42] and time-resolved conductivity [43]. Although all probing methods reflect the influence of pump-excited carriers on semiconductor properties, only 2PPES and one-photonpumped TA spectroscopy (1PPTAS) allow one to study the evolution of the electron energy distribution function (EDF) during the relaxation process [14][15][16][17][18][19][20][21][22][23]37]. In addition to elucidating the carrier cooling mechanism, EDF also provides valuable information about the possible states of carriers in semiconductor devices.…”
Section: Introductionsupporting
confidence: 62%
“…Specifically, the combination of angular and time resolution in 2PPES allows one to study the time evolution of EDF for a population of photoexcited electrons in the conduction band relative to their crystal momentum. Using this method, the dynamics of photoexcited electrons in the conduction band of 2D materials have been studied [14][15][16][17][18][19][20][21][22][23].…”
Section: The Basic Concepts Of Multiphoton-pumped Uv-vis Ta Spectroscopymentioning
confidence: 99%
“…In addition, ultrafast carrier dynamics and excitonic effects have recently been investigated using the tr-ARPES technique [438]. These include graphene [439][440][441][442][443], BP [444][445][446][447], Bi 2 Se 3 [263,[448][449][450][451][452][453][454][455][456], TMDCs [5,278,[457][458][459][460][461][462][463][464][465] and 2D CDW TaS 2 [105,110,[466][467][468][469] systems.…”
Section: Two-dimensional Materialsmentioning
confidence: 99%
“…In this review, we focus on arguably the most significant innovations in the field of photoemission from a rather technical perspective. More specialized reviews of ARPES studies of quantum materials can be found in [5][6][7][8][9]. The manuscript is organized as follows: First, we provide a brief introduction to the fundamental theory of the photoemission process, discuss experimental matters connected to photon energy, and reflect on sample requirements.…”
Section: Introductionmentioning
confidence: 99%
“…In many regards, QSR is akin to the renormalization of the band-edge states characterized in the monolayer transition metal dichalcogenides (TMDCs). Time- and angle-resolved photoemission spectroscopy experiments performed on room-temperature monolayer MoS 2 directly probed the electronic structure renormalization induced with low excitation fluences. , The band-edge states of the MoS 2 sample were observed to shift by ∼40 meV to higher energies at the K point, k = −1.29(1) Å –1 , upon photoexcitation with low fluences, followed by a recovery within 5.0(1.8) ps. The excitation energy at the K valley edge, k = −1.14(1) Å –1 , was observed to decrease by ∼100 meV, and this perturbation remained for much longer than that at the K point.…”
Section: Introductionmentioning
confidence: 99%